Nrf2 modulates the benefits of evening exercise in type 2 diabetes - Babatunde Fasipe; Ismail Laher (Sports Medicine and Health Science, 2023)
Exercise has well-characterized therapeutic benefits in the management of type 2 diabetes mellitus (T2DM). Most of the beneficial effects of exercise arise from the impact of nuclear factor erythroid 2 related factor-2 (Nrf2) activation of glucose metabolism. Nrf2 is an essential controller of cellular anti-oxidative capacity and circadian rhythms. The circadian rhythm of Nrf2 is influenced by circadian genes on its expression, where the timing of exercise effects the activation of Nrf2 and the rhythmicity of Nrf2 and signaling, such that the timing of exercise has differential physiological effects. Exercise in the evening has beneficial effects on diabetes management, such as lowering of blood glucose and weight. The mechanisms responsible for these effects have not yet been associated with the influence of exercise on the circadian rhythm of Nrf2 activity. A better understanding of exercise-induced Nrf2 activation on Nrf2 rhythm and signaling can improve our appreciation of the distinct effects of morning and evening exercise. This review hypothesizes that activation of Nrf2 by exercise in the morning, when Nrf2 level is already at high levels, leads to hyperactivation and decrease in Nrf2 signaling, while activation of Nrf2 in the evening, when Nrf2 levels are at nadir levels, improves Nrf2 signaling and lowers blood glucose levels and increases fatty acid oxidation. Exploring the effects of Nrf2 activators on rhythmic signaling could also provide valuable insights into the optimal timing of their application, while also holding promise for timed treatment of type 2 diabetes.